Entwicklungslinien der beruflichen Fachrichtung Sozialpädagogik und einer Didaktik der Sozialpädagogik: Perspektiven einer scientific community im Werden - Bobe, Anna; Göddertz, Nina; Karber, Anke; Paesche, Moritz; Schmökel, Michelle Jaquelina; Schwertfeger, Anja; Seltrecht, Astrid (bwp@ Spezial HT2025: Nachhaltig – Digital – Chancengerecht. Zukunftsszenarien von Arbeit, Bildung und Beruf)

ABIS 2026: The Effects of the Adaptive Web on Society - Stojko, Laura; Herder, Eelco; Strecker-Bischoff, Jannis; Sänger, Julia Seitz; Neumayr, Thomas; Yigitbas, Enes; Augstein, Mirjam (Companion Publication of the 2026 18th ACM Web Science Conference, WebSci Companion 2026, Braunschweig, Germany, May 26-29, 2026)

bwp@ Spezial HT2025: Nachhaltig – Digital – Chancen gerecht. Zukunftsszenarien von Arbeit, Bildung und Beruf

Stereotype Darstellungen im Bild. Analyse von Bildmaterial digital verfügbarer Unterrichtsmaterialien - Schmidt, Rebecca; Drath, Hannah; Steinhardt, Isabel (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Lehrer:innen nutzen und veröffentlichen Unterrichtsmaterial auf verschiedenen Plattformen. Da diese Materialien, anders als Schulbücher, kein Qualitätssicherungsverfahren durchlaufen, wird aktuell die Frage nach der Verantwortung für die Qualitätssicherung dieses Materials diskutiert. Abbildungen von Menschen im Unterrichtsmaterial transportieren soziokulturelle und pädagogische Inhalte, die eine kritische Prüfung erfordern. Dieser Beitrag adressiert die Frage, welche Differenzkonstruktionen und Stereotypisierungen im Bildmaterial von digital verfügbarem Unterrichtsmaterial vorhanden sind. Verwendet wurde ein Materialkorpus drei verschiedener Plattformen mit Unterrichtsmaterialien der Sekundarstufe 1 (5. – 10. Klasse) mit 329 Bildern von Menschen (Zeichnungen und Fotografien). Dieser wurde analysiert in Bezug auf die deskriptive Häufigkeit der Darstellung bestimmter Personengruppen sowie qualitativ und intersektional mit der hermeneutischen Sequenzanalyse. Zentrale Ergebnisse sind, dass vor allem Personen dargestellt werden, die in maximal einer Dimension von der weissen, heterosexuellen, nicht behinderten Norm abweichen. Darstellungen von sichtbaren Behinderungen und People of Color (BIPoC) kommen kaum vor. Diversität wird vereinzelt in Gruppenbildern dargestellt, jedoch nicht in Familienbildern. Othering und negative emotionale Konnotationen sind in den Darstellungen erkennbar, wenn z. B. Schwarzsein als Abweichung von der Norm verstanden wird, Körperproportionen verzerrt oder Sportler:innen als unsicher dargestellt werden. Die Analyse von digital bereitgestelltem Unterrichtsmaterial macht deutlich, dass ähnliche Problematiken zu beobachten sind, wie sie durch die Schulbuchforschung für Schulbücher beschrieben werden.

Spatially Uniform and Defect‐Tolerant Plasmonic Responses in 3D Printed Gold Nanoparticle Assemblies - Devaraj, Vasanthan; Kwak, Sunghyun; Kim, Hyeongjip; Sung, Sang‐Keun; Lee, Jong‐Min; Zentgraf, Thomas; Kim, Won‐Geun (Laser & Photonics Reviews)
Three‐dimensional (3D) assemblies of gold nanoparticles (AuNPs) offer a rich platform for plasmonic coupling and near‐field engineering, yet their optical behavior is often complex due to structural disorder and fabrication‐induced variability. Here, we present a systematic optical investigation of large‐scale 3D AuNP assemblies fabricated via meniscus‐guided assembly, focusing on the reproducibility, spatial uniformity, and mode evolution of their plasmonic responses. Spatially‐resolved dark‐field scattering measurements reveal that high‐aspect‐ratio AuNP pillars exhibit uniform scattering spectra along their height and across different pillars, despite variations in geometry and structure. Electromagnetic simulations suggest that this robustness arises from a collective many‐particle plasmonic response that remains optically active despite structural perturbations. The corresponding near‐field and surface‐charge distributions remain spatially distributed under representative structural perturbations, consistent with volumetric averaging across the three‐dimensional assembly. Building on this robust platform, we introduce compositional modulation through a core–satellite architecture by incorporating smaller AuNPs. This yields a composition‐dependent spectral redistribution, including the emergence of an additional long‐wavelength spectral feature in the core–satellite assemblies. Wavelength‐dependent surface‐enhanced Raman scattering measurements reveal contrasting responses under 633 and 785 nm excitation, reflecting redistribution of local plasmonic coupling pathways. These results provide process‐enabled guidelines for using meniscus‐guided 3D‐nanoprinting to realize robust nanoparticle assemblies.

“The city isn’t uploading me to TikTok”: Exploring Privacy Attitudes towards Data Collection in Urban Public Spaces - Todt, Julian; Kablo, Emiram; Morsbach, Felix; Arias Cabarcos, Patricia; Strufe, Thorsten (Proceedings on Privacy Enhancing Technologies)
Smart cities promise safer streets, smoother traffic, and more efficient services, enabled by dense networks of urban sensors. Yet this infrastructure, often unnoticed by citizens, introduces pervasive privacy risks, from tracking, profiling, and sensitive inferences to subtle forms of self-censorship. Despite widespread deployment, little is known about how the public understands and perceives these sensing systems. To address this gap, we present an intervention based user study (n = 172) in which participants are exposed to data collection by six urban sensors, including cameras and alternative technologies commonly framed as privacy-preserving. Participants encounter either the sensors alone or sensors accompanied by real-time data visualizations. Our results reveal widespread misunderstanding of some sensors (radar, LiDAR, Wi-Fi, depth, and thermal imaging sensors), particularly their capacity for identification and for attribute inferences such as gender or age. We also identify persistent misconceptions, including the belief that Wi-Fi poses privacy risks only when users connect to public networks. While making sensors visible and visualizing collected data improves privacy awareness, these measures alone are not enough for citizens to understand the actual risks of urban sensing. We derive recommendations for privacy-respecting smart city environments grounded in citizens’ informational needs and expectations.

Inscription of power dynamics in platformized classrooms. Exploring coded spaces of platform architectures through Participatory Action Research - Schmidt, Rebecca (Learning, Media and Technology)
Platforms contribute to the ‘world-making’ of education; they play a co-constitutive role by envisioning and inscribing the functionalities anticipated in education. As programmable digital architectures, they both shape and are shaped by teachers’ and students’ practices. Building on two Action Research projects in German schools, the article concentrates on the reproduction of inequality within platformized classrooms. It uses the focus point of translation software usage to explore inscriptions into digital architectures. Analysing breakdowns of translation software usage among students who speak German as a second/foreign language, the article focuses on inscribed power dynamics within translation software, the mismatch between students’ practices and the imagined user, and the discrepancy between software logics and the educational setting. Discussing teachers’ invisible work, care and belonging in platformized education settings, the article highlights the epistemic inscriptions within technology. It describes how dataveillance and testing break down when students use translation software, thereby highlighting teachers’ shift towards creating a collective understanding. Lastly, the article discusses teachers’ autonomy within post-platform education by highlighting the limitations of currently available software products and software production.
Keywords: Intersectionality; platform studies; action research; post-platform education; breakdowns; translation software; classroom reserach

"I store some passwords in WhatsApp": Understanding User Experiences and Usability Challenges of Password Managers in Virtual Reality - Kablo, Emiram; Sharafi, Avishan; Arias Cabarcos, Patricia (Proceedings of the Extended Abstracts of the 2026 CHI Conference on Human Factors in Computing Systems)

Shapes from Examples: Foundations of Shape Learning in Recursive SHACL - Gortworst, Bente; Okulmus, Cem; Ortiz, Magdalena; Turhan, Anni-Yasmin (Proceedings of the 25th International Semantic Web Conference (ISWC 2026))

Position, Positionierungen und Positionalität im Religionsunterricht im Unterrichten über Religionen, denen man nicht angehört Autor/innen - Keuchen, Marion; Ta Van, Juliane; Tuna, Mehmet H (TheoWeb. Zeitschrift für Religionspädagogik)
Der Beitrag untersucht Kurzfilme als Kommunikations-, Kompensations- und Diskursmedien im Religionsunterricht und entwickelt eine kritische Kurzfilmhermeneutik. Ausgangspunkt ist die Beobachtung, dass Kurzfilme im Unterricht häufig inhaltlich verengt und primär als Mittel zur Themenvermittlung genutzt werden. Demgegenüber betonen die Autor:innen die spezifische Ästhetik, Mehrdeutigkeit und mediale Komplexität des Kurzfilms. Zentrale Kategorien sind dabei das Zusammenspiel von „story“ und „discourse“ sowie inter-, intra- und transmediale Bezüge. Kurzfilme eröffnen durch Verdichtung, Leerstellen und offene Enden eigenständige Zugänge zu Sinnfragen und fördern aktive Rezeptionsprozesse. Anhand des Films „YELLOW“ wird gezeigt, wie filmische Gestaltungselemente Bedeutung generieren und gesellschaftlich-religiöse Diskurse anstoßen. Eine kritische Kurzfilmhermeneutik erweitert somit die Filmdidaktik, indem sie das Medium selbst stärker in den Fokus rückt. Ziel ist eine reflektierte, medienkompetente und dialogorientierte Nutzung von Kurzfilmen im Religionsunterricht.
Keywords: interreligiöses Lernen; Religionsunterricht; Positionierung; Islam; Christentum; Unterrichtsbeobachtung; Position; Fremdheit

Potenziale der Portfolioarbeit für den Aufbau vernetzten Wissens im Bachelorstudium: Eine Explorationsstudie im Studienfach Komparatistik/Vergleichende Literatur- und Kulturwissenschaft - Hannebohm, Ronja (die hochschullehre: Interdisziplinäre Zeitschrift für Studium und Lehre)
Vernetztes Wissen ist ein zentrales Lernziel des Hochschulstudiums, insbesondere im interdisziplinär angelegten Studienfach Komparatistik. Um den Aufbau vernetzten Wissens bei Bachelorstudierenden der Komparatistik zu unterstützen, ist in diesem Projekt Portfolioarbeit eingesetzt worden, die als Methode selbsttätigen und selbstreflexiven Lernens geeignet erscheint, zur Auseinandersetzung mit Lerninhalten zu motivieren und zur Kompetenzentwicklung der Studierenden beizutragen. Mittels unstrukturierter Beobachtungen der Portfolioarbeit im Seminar sind inhaltliche Effekte und methodische Entwicklungen erfasst worden. Anhand anteilig quantitativer, überwiegend qualitativer Inhaltsanalysen der Portfolios sind konkrete Vernetzungen zwischen Lerninhalten ermittelt worden. Die Explorationsstudie zeigt veränderte Perspektiven und geweckte Interessen bei den Studierenden durch die Portfolioarbeit sowie vielfältige Kontextualisierungen, Vergleiche und Verknüpfungen in den Portfolios auf und bietet hierdurch einen möglichen Ansatzpunkt für strukturelle Empfehlungen für das Studienfach Komparatistik.
Keywords: Portfolioarbeit; portfolio work; vernetztes Wissen; knowledge networks; Beobachtung; naturalistic observation; Inhaltsanalyse; content analysis

Kurzfilme als Kommunikations-, Kompensations-, Diskurs- und Inter-/Intramedien. Eine kritische Kurzfilmhermeneutik für den Religionsunterricht - Karsch, Manfred; Keuchen, Marion; Weber, Astrid (TheoWeb. Zeitschrift für Religionspädagogik)
Der Beitrag untersucht Kurzfilme als Kommunikations-, Kompensations- und Diskursmedien im Religionsunterricht und entwickelt eine kritische Kurzfilmhermeneutik. Ausgangspunkt ist die Beobachtung, dass Kurzfilme im Unterricht häufig inhaltlich verengt und primär als Mittel zur Themenvermittlung genutzt werden. Demgegenüber betonen die Autor:innen die spezifische Ästhetik, Mehrdeutigkeit und mediale Komplexität des Kurzfilms. Zentrale Kategorien sind dabei das Zusammenspiel von „story“ und „discourse“ sowie inter-, intra- und transmediale Bezüge. Kurzfilme eröffnen durch Verdichtung, Leerstellen und offene Enden eigenständige Zugänge zu Sinnfragen und fördern aktive Rezeptionsprozesse. Anhand des Films „YELLOW“ wird gezeigt, wie filmische Gestaltungselemente Bedeutung generieren und gesellschaftlich-religiöse Diskurse anstoßen. Eine kritische Kurzfilmhermeneutik erweitert somit die Filmdidaktik, indem sie das Medium selbst stärker in den Fokus rückt. Ziel ist eine reflektierte, medienkompetente und dialogorientierte Nutzung von Kurzfilmen im Religionsunterricht.
Keywords: Film; Religionsunterricht; Fachdidaktik; Hermeneutik

Nach 1984: Biopoethik des eugenetischen Romans - Hannebohm, Ronja
Was bedeutet es, ‚Mensch‘ zu sein im Zeitalter des entschlüsselten Genoms? Der eugenetische Roman ist als ein literarisches Genre zu begreifen, das biowissenschaftliche, bioethische und biopoetische Dimensionen miteinander verbindet, um ebendiese Frage auszuloten und hierbei Grenzen und Konstanten des Mensch(lich)en auszuhandeln. Mindestens seit Darwin und Galton sind die Modifizierung des menschlichen Individuums und die Optimierung der menschlichen Spezies diskutiert worden, spätestens seit den 1980er Jahren haben humangenetische und biotechnologische Entwicklungen den Diskurs neu perspektiviert. Literatur trägt zu diesem Diskurs bei, indem sie Erprobungs- und Reflexionsräume schafft: Sie modelliert menschliche Subjekte, die in eugenetische Zukunftsszenarien eingeschrieben sind, und entwickelt spezifische Erzählweisen, die diese Subjekte, ihre Lebensweisen und ihr Lebenswissen narrativ erfahrbar machen. Fünf eugenetische Romane der englisch- und deutschsprachigen Gegenwartsliteratur von Margaret Atwoods „The Handmaid’s Tale“ (1985) bis Emma Braslavskys „Leben ist keine Art, mit einem Tier umzugehen“ (2016) werden in der Studie hinsichtlich Subjektmodellierungen und Narrationsweisen im Kontext der Eugenetik untersucht.
Keywords: Ethik; Eugenik; Genre; Lebenswissen; Macht; Metamoderne; Narration; Postmoderne; Subjekt; Zukunft

Skills Help, but They Don’t Help All at Once: Changes in the Relationship Between Study- Relevant Skills and Student Stress as Well as Study Satisfaction During the First Two Years of Teacher Education - Sagolla, Nils; Seifert, Andreas; Bohndick, Carla; Buhl, Heike M. (Journal for Educational Research Online)

Ongoing efforts to enhance stability - Keller, Adrian Clemens (Nucleic Acid Insights)
Over the last few decades, a large variety of nucleic acid‑based therapeutic approaches and drug formulations have been developed in the lab, tested in the clinic, and brought to market, ranging from antisense oligonucleotides (ASOs) and siRNAs to aptamer inhibitors and mRNA vaccines, with DNA and RNA nanostructure therapeutics already looming on the horizon. However, being susceptible toward hydrolysis, oxidation, non‑specific binding, and nuclease digestion, unmodified nucleic acids are rapidly degraded in vivo, resulting in poor therapeutic performance. Therefore, several stabilization strategies have been developed in order to protect those fragile molecules against adverse conditions during storage and in the body, while simultaneously accommodating their various mechanisms of action such as cellular uptake, target binding, or translation. These strategies include chemical modifications at the nucleoside level, complexation with proteins and polymers, and encapsulation in lipid nanoparticles (LNPs). Despite this variety of available methods, the field still faces many challenges, and this issue aims to provide an overview of the ongoing efforts to enhance the stability of therapeutic nucleic acids.

Digging to the Ground Truth: Solving Multi-objective Gray-Box Optimization Problems through Hyperplane Elimination - Mensendiek, Carolin; Preuß, Oliver Ludger; Rook, Jeroen; Chicano, Francisco; Whitley, Darrell; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference, GECCO 2026, Centro Internacional de Convenciones CIC-ANDE, San Jose, Costa Rica, July 13-17, 2026)

Partner models of explainers: a qualitative interview study - Gladow, Viviane; Buhl, Heike M. (Frontiers in Education)

Conceptualising Risk and Risk Literacy—results of a Delphi Study Konzeptualisierung von Risiko und Risikokompetenz – Ergebnisse einer Delphi-Studie - Eichler, Andreas; Büchter, Theresa; Binder, Karin (Journal für Mathematik-Didaktik)
Abstract Risk is an integral part of modern societies and therefore school education, and in particular mathematics education, should develop students’ risk literacy. Students’ risk literacy is part of the interdisciplinary research project siMINT (Understanding complex STEM topics: Using simulations to promote competences for the 21st century). One first challenge in this project was to find a common ground for the inconsistently conceptualised terms of risk and risk literacy. Consequently, the aim of this paper is to contribute to the conceptualisation of risk and risk literacy. The first part of this paper provides a literature review on these areas, resulting in a working conceptualisation of the two concepts. We further carried out two consecutive steps of a Delphi study with N = 15 and N = 12 experts respectively, to develop a common conceptualisation based on the plurality of different dimensions and elements of risk and risk literacy. Based on the results of the first step of the Delphi study, we modified our working conceptualisation, using a common model of risk and risk literacy with different dimensions. In the second step of the Delphi study, the experts comment on (i) the dimensions and (ii) the elements of risk and risk literacy in these dimensions. The results showed that the experts are able to locate their individual definitions of risk in the model with three dimensions (relation between risk/uncertainty, connotation, and mathematical object) that we developed and to formulate reasons for their allocation. Furthermore, the results revealed that risk literacy consists of subsets of mathematical and non-mathematical elements that the experts rate differently with regard to their importance. In general, the results contribute to clarifying the constructs of risk and risk literacy as a basis for developing approaches to improve risk literacy.

Evaluation des Buddy-Programms der GDCP-Jahrestagung 2025 - Zwick, Linda; Bühler, Eva; Weiler, David Christoph (KI in der naturwissenschaftlichen Bildung)
Der Erfolg von Wissenschaftler:innen in frühen Karrierephasen (WiKa) hängt von vielen Faktoren ab, wobei die wissenschaftliche Gemeinschaft ein entscheidender Faktor sein kann (Cornér et al., 2018; Corceslles et al., 2019; Corcelles-Seuba et al., 2023). Vor diesem Hintergrund ist es wichtig, dass die wissenschaftliche Gemeinschaft gezielte Unterstützungsangebote für WiKa bereitstellt, in denen sie neben dem fachlichen Austausch auch Möglichkeiten zur Vernetzung und sozialen Unterstützung haben. Die WiKa der GDCP haben 2023 mit dem Buddy-Programm auf der Jahrestagung begonnen, um Wissenschaftler:innen zu Beginn ihrer Promotionszeit ein strukturiertes Unterstützungsangebot bereitzustellen. Das Buddy-Programm wurde in den folgenden Jahren basierend auf den Rückmeldungen der Teilnehmenden weiterentwickelt. In diesem Beitrag werden die Evaluationsergebnisse des Buddy-Programms während der Jahrestagung 2025 vorgestellt und diskutiert.
Keywords: GDCP; Buddy-Programm; Evaluation

The integration of probability-based arguments in risk-related contexts - Büchter, Theresa; Binder, Karin; Eichler, Andreas (Proceedings of the IASE 2025 Satellite Conference - Statistics and Data Science Education in STEAM)